2011
DOI: 10.1016/j.joca.2010.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of the NF-κB pathway for induction of Wnt-5A by interleukin-1β in condylar chondrocytes of the temporomandibular joint: functional crosstalk between the Wnt-5A and NF-κB signaling pathways

Abstract: These results clarify the molecular mechanism underlying up-regulation of Wnt-5A by IL-1β in chondrocytes, suggesting an important functional crosstalk between Wnt-5A and NF-κB signaling pathways. This finding provides new insights into the involvement of Wnt signaling in the cartilage destruction caused by arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 42 publications
5
61
0
Order By: Relevance
“…1A) strongly suggested the presence of another signaling pathway downstream of IL-1␤ that could enhance migration in human CECs. Several reports linking IL-1␤ with Wnt5a signaling led us to investigate its potential as a candidate (44,54,55). Expression of Wnt5a has been reported in fetal but not adult corneal endothelium in humans (34), and this is consistent with our Western blot analysis results, where Wnt5a could not be detected in differentiated human CECs in vitro (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…1A) strongly suggested the presence of another signaling pathway downstream of IL-1␤ that could enhance migration in human CECs. Several reports linking IL-1␤ with Wnt5a signaling led us to investigate its potential as a candidate (44,54,55). Expression of Wnt5a has been reported in fetal but not adult corneal endothelium in humans (34), and this is consistent with our Western blot analysis results, where Wnt5a could not be detected in differentiated human CECs in vitro (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…It has been reported that IL-1␤ can induce Wnt5a expression through NF-B in chondrocytes (44). Moreover, NF-B has been reported to bind and activate the human Wnt5a promoter (45).…”
mentioning
confidence: 99%
“…2), proinflammatory microglia might provoke Ror2 expression in spinal neurons of the gray matter. Although it remains unclear how inflammatory cytokines elicit Ror2 expression in the spinal neurons, previous reports have demonstrated that IL-1␤ induces noncanonical Wnt5a expression via NF-B in chondrocytes and that NF-B can bind to the human Wnt5a promoter (54,55). It is possible that inflammatory cytokines recruit transcription factors, such as NF-B or AP-1, to induce Wnt11 or Ror2 expression in spinal neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Because it has been reported that WNT5A expression could be regulated by NF-κB, 27 we were interested in assessing whether PGRN deficiency influences NF-κB activity. Fig.…”
Section: Nf-κb Is Overactivated In Pgrn-deficient Lymphoblastsmentioning
confidence: 99%
“…27 In this sense, 2 promoter regions have been identified in the human WNT5A gene (promoter A and B), which contains putative NF-κB binding sites. 28 NF-κB mediates the expression of many genes involved in inflammation and it is known to be upregulated in some neurodegenerative disorders such as Alzheimer disease, 29,30 Parkinson disease 31 or amyotrophic lateral sclerosis (ALS).…”
Section: Introductionmentioning
confidence: 99%